A comparative remark on heat transfer in thermally stratified MHD Jeffrey fluid flow with thermal radiations subject to cylindrical/plane surfaces. (April 2022) - Ur Rehman, Khalil; Shatanawi, Wasfi; Al-Mdallal, Qasem M.
Abstract: We have observed that the various individual heat transfer findings exist in the literature for both Newtonian and non-Newtonian fluids through the plane and cylindrical surfaces. These efforts contain specific thermophysical observations and one can get facilitated in one frame at a time. Therefore, in the present attempt, we execute a comparative heat transfer study because the unifying of different theories always receive appreciation from the research community. To support the idea, we considered convective magnetized and thermally stratified Jeffrey flow fields over inclined cylindrical and plane surfaces with and without non-linear thermal radiations. Stagnation point flow equations are constructed for cylindrical/plane surfaces in the presence of heat generation and heat absorption effects. The shooting method is used to solve reduced ordinary differential equations. We come to conclude that the Jeffrey fluid flow over a cylindrical surface subject to magnetic field parameter is large in magnitude in comparison with a plane surface. The strength of the temperature regime and heat transfer rate are also enriched for the cylindrical surface. Collectively, we come to know as a remark that thermophysical flow field aspects are enriched for magnetized stratified convective flow towards the cylindrical surface as compared to a plane surface.